Prospects for the Use of Social Media Marketing Instruments in Health Promotion by Polish Marshal Offices - Magdalena Syrkiewicz-S´witała; Piotr Romaniuk; Agnieszka Strzelecka; Katarzyna Lar; Tomasz Holecki (Frontiers Media S.A., 2018)
PurposeTo investigate whether the Polish Marshal Offices use instruments for social media marketing activities in the field of health promotion.Methodology14 Polish Marshal Offices participated. The Computer-Assisted Web Interview and Computer-Assisted Telephone Interview were used along with a proprietary questionnaire. Standard statistical methods were employed.FindingsThe number of people using the Internet and social media in Poland is steadily growing. The majority of the offices (93%) performed health promotion activities. The authorities collaborated with other units of local government and non-governmental organizations in these activities. According to respondents, the most convincing form of health promotion is direct communication (46%). More than half of the surveyed offices (56%) did not use portals or social networking sites in health campaigns. The rest of the offices indicated using Facebook (25%) or YouTube (6%). Half of them did not apply the tools of social media marketing. The other half was involved in discussions on health-related online forums (moderation or consulting). Relatively few offices use social media and social media marketing in health promotion campaigns.ValueThe use of social media by the Marshal Offices may result in a potential increase in effectiveness of the pro-health campaigns. It is recommended that Polish Marshal Offices recognize the potential benefits of social media marketing campaign instruments in the field of health promotion in order to reach out the digital recipients.